Correction of carbohydrate metabolism in the use of a cybernetic complex of insulin therapy after transplantation - O. N. Rzhevskaya; V. K. Novikov; K. E. Lazareva (Трансплантология (Москва), 2018)
The paper describes the use of the artificial pancreatic analogue – a cybernetic complex of insulin therapy – to correct carbohydrate metabolism in patients with diabetes mellitus in the early postoperative period after cadaveric renal allotransplantation.